The Language Style Used By Merry Riana In The Youtube Podcast Channel - Ningsih, Devi Widya (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
Some people have a special style of presenting information. Language style is the way a person conveys information in interesting language, both orally and in writing, to give a good impression to each listener or reader. It is very important for some people to express their thoughts or ideas. Generally, someone uses language styles depending on who and where they communicate. The form of language can be spoken and written which involves expressing and patterning choices of opinion and choosing forms, in order to convey the message intended by the speaker. This research was conducted to analyze Merry Riana's language style on her YouTube channel. This focuses on the language style used in Merry Riana's podcast YouTube channel. He is a motivator and also a YouTuber who has many subscribers from the millennial generation. He has an interesting concept in his motivation. The design of this research is descriptive qualitative. Based on these findings, researchers concluded that Merry Riana mostly uses casual style (52%), formal style (30%) and intimate style (18%) in her podcast